Direct One‐pot Synthesis of Carbon Supported Ag‐Pt Alloy Nanoparticles as High Performance Electrocatalyst for Fuel Cell Application. Issue 2 (28th March 2019) - Fu, T.; Zhang, S.; Huang, J.; Cai, D.; Li, J.; Zhao, J.
Abstract: Ag‐Pt alloy material is one of the most potential candidates to improve the catalytic activity of Pt‐based catalyst toward the oxygen reduction reaction (ORR), which can reduce the dosage of the high‐cost metal Pt used in the cathode of fuel cells. But it is hard to synthesis Ag‐Pt alloy with nanosize in an easy and cheap way. In this study, the Ag‐Pt alloy nanoparticles supported on carbon (Ag‐Pt/C) with different Ag at.% were prepared by a facile one‐pot approach with low costs. The XRD, TEM and XPS measurements were applied to verify the alloy structure of Ag‐Pt nanoparticles. These Ag‐Pt/C samples showed enhanced mass activities and catalytic stabilities for the ORR, which was up to two times higher than that of the commercial Pt/C catalyst at 0.9 V ( vs. reversible hydrogen electrode). Furthermore, the membrane electrode assembly (MEA) made from the Ag‐Pt/C catalyst also showed a higher power density in H2 ‐O2 fuel cell test compared to the MEA made from the commercial Pt catalyst. These enhancements are attributed to the higher utilization of Pt and the regulated oxygen adsorption energy of Pt in the surface, which was confirmed using the density function theory calculation.